«Руська» термінологія в Київському та Галицько-Волинському літописних зводах - Моця, О.П. (Інститут археології НАН України, 2009)
Зіставлено тексти двох літописних зводів, що дало змогу простежити розширення зони використання «руської» назви із земель Середнього Подніпров’я до Прикарпаття. В статье рассмотрен вопрос об использовании названий «Русь»/«Русская земля» в двух источниках ХІІ и ХІІІ вв. - Киевском и Галицко-Волынском летописных сводах, которые формировались в центрах Среднего Поднепровья и карпатском регионе соответственно. В результате было установлено, что первоначально Галич не входил в историко-территориальную «русскую зону» (как и северные, а также поволжские регионы восточнославянского мира). Только со времен Романа Мстиславича и Данила Романовича ситуация кардинально изменилась и «русское» название надолго укрепилось в карпатском регионе. The article views the issue of usage of names Rus/Rus Land in two sources of the 12th and the 13th centuries — Kyiv and Halych-Volyn annalistic codes, developed correspondingly in the centres of the Middle Dnipro River region and the Carpathian region. As a result of carried out work it was established that initially Halych did not belong to the historic and territorial «Ruthenian zone» (as well as the Northern and the Volga River regions of the Eastern Slav world). Only since the time of Roman Mstyslavovych and Danylo Romanovych the situation radically changed, and the «Ruthenian» name for long became customary in the Carpathian region.